Republic of Madagascar : Enhanced Initiative for Heavily Indebted Poor Countries Completion Point Document. (IMF Staff Country Reports; Country Report ;, 2004)
This paper reviews Madagascar's progress under the Heavily Indebted Poor Countries (HIPC) Initiative. Total assistance to be provided to Madagascar under the HIPC Initiative amounts to USD 836 million in net present value terms-USD 22 million higher than the decision point estimate. The paper assesses Madagascar's performance in meeting the requirements for reaching the completion point, as set out in the decision point document. The paper also reviews the status of creditor participation and the delivery of debt relief to Madagascar under the enhanced HIPC Initiative. It also presents results of the updated Debt Sustainability Analysis.